2021
DOI: 10.1093/nar/gkab696
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule/particle tracking analysis program SMTracker 2.0 reveals different dynamics of proteins within the RNA degradosome complex inBacillus subtilis

Abstract: Single-molecule (particle) tracking is a powerful method to study dynamic processes in cells at highest possible spatial and temporal resolution. We have developed SMTracker, a graphical user interface for automatic quantifying, visualizing and managing of data. Version 2.0 determines distributions of positional displacements in x- and y- direction using multi-state diffusion models, discriminates between Brownian, sub- or superdiffusive behaviour, and locates slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 48 publications
3
60
0
Order By: Relevance
“…Thus, the components of the Y-complex behave similarly towards rifampicin treatment, corresponding to the finding of complex formation by the three proteins [18]. It has been shown that RNase Y still forms foci at the cell membrane after inhibition of transcription [20], but that RNase Y relocalizes from the membrane towards to cytosol [32]. Because there is a dispute over whether SMT data on RNase Y are valid, we will perform additional control experiments before further proceeding with a comparison between RNase Y and Y-complex protein dynamics in a future study.…”
Section: Localization Of the Y-complex In Live B Subtilis Cellsmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, the components of the Y-complex behave similarly towards rifampicin treatment, corresponding to the finding of complex formation by the three proteins [18]. It has been shown that RNase Y still forms foci at the cell membrane after inhibition of transcription [20], but that RNase Y relocalizes from the membrane towards to cytosol [32]. Because there is a dispute over whether SMT data on RNase Y are valid, we will perform additional control experiments before further proceeding with a comparison between RNase Y and Y-complex protein dynamics in a future study.…”
Section: Localization Of the Y-complex In Live B Subtilis Cellsmentioning
confidence: 59%
“…For Northern blot analysis, RNA samples were mixed with 2× PAGE loading dye (1× TBE in formamide containing xylene cyanol and bromphenol blue). 32 P-labelled HR RiboRuler Ladder (Thermo Fisher Scientific, Walthman, MA, USA) was prepared using 20 µl HR RiboRuler Ladder, 40 µCi of γ-32 P-ATP (Hartmann Analytik GmbH, Braunschweig, Germany), 1× Buffer A (Thermo Fisher Scientific, Walthman, MA, USA) and 20 U PNK (Thermo Fisher Scientific, Walthman, MA, USA) at 37 • C for 1 h. Total RNA was fractionated by agarose gel electrophoresis (1.2% agarose, 0.6% formaldehyde v/v, 1× MOPS buffer, pH 7) at 110 V. Using a capillary transfer, RNA was transferred from the agarose gel to Whatman Nytran SuPerCharge nylon blotting membrane (GE Healthcare, Chicago, IL, USA) in 10× SSC buffer, pH 7 overnight. The membrane was UV cross-linked and prehybridized in 20 ml ROTI ® Hybri-Quick (Carl Roth, Karlsruhe, Germany) for 30 min at 45 • C. 10 µl of previously radiolabeled RNA riboprobes were added to the prehybridized membrane and incubated for 3 h at 45 • C. The blots were washed twice for 20 min with wash solution 1 (2× SSC, 0.1% SDS w/v) and twice for 20 min with wash solution 2 (0.1× SSC, 0.1% SDS w/v) at 45 • C. Results were visualized using storage phosphor screens (GE Healthcare, Chicago, IL, USA) and Typhoon TM biomolecular imager (GE Healthcare, Chicago, IL, USA).…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…To identify differences in protein mobility and/or behavior, the resulting tracks were subjected to dwell time, mean-squared-displacement (MSD), and square displacement (SQD) analysis in SMTracker 2.0 [ 49 ], described previously [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Exponentially growing cells of B. subtilis (left/cyan panels) (BHF073) or C. glutamicum (right/magenta panels) (B6G8) expressing a DivIVA-Halo fusion, respectively, were stained with TMR (HaloTag ligand). Individual protein trajectories were recorded via single-molecule localization microscopy and analyzed using Trackmate [ 48 ] and the SMTracker [ 49 ] software packages. ( A ) Representative cells of B. subtilis and C. glutamicum displaying confined (blue) and fast (red) trajectories of DivIVA-Halo.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation